2022
DOI: 10.1186/s12985-022-01842-x
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced synergistic antitumor effect of a DNA vaccine with anticancer cytokine, MDA-7/IL-24, and immune checkpoint blockade

Abstract: Background MDA-7/IL-24 cytokine has shown potent antitumor properties in various types of cancer without exerting any significant toxicity on healthy cells. It has also been proved to encompass pro-immune Th1 cytokine-like behavior. Several E7 DNA vaccines have developed against human papillomavirus (HPV)-related cervical cancer. However, the restricted immunogenicity has limited their clinical applications individually. To address this deficiency, we investigated whether combining the E7 DNA v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 63 publications
0
5
0
Order By: Relevance
“…However, nucleic acid‐based vaccines have limited immunoprototypes, which curtails their utility. Nonetheless, preclinical studies have demonstrated that the incorporation of adjuvants such as MDA‐7/IL‐24/IL‐7/GM‐CSF, immune checkpoint blockers, and chitosan nanoparticles enhances the functionality of DNA vaccines 319–322 . A noteworthy example of therapeutic DNA‐based vaccines is VGX3100, which comprises two DNA plasmids encoding HPV16/18 E6/E7 proteins.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, nucleic acid‐based vaccines have limited immunoprototypes, which curtails their utility. Nonetheless, preclinical studies have demonstrated that the incorporation of adjuvants such as MDA‐7/IL‐24/IL‐7/GM‐CSF, immune checkpoint blockers, and chitosan nanoparticles enhances the functionality of DNA vaccines 319–322 . A noteworthy example of therapeutic DNA‐based vaccines is VGX3100, which comprises two DNA plasmids encoding HPV16/18 E6/E7 proteins.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“…Nonetheless, preclinical studies have demonstrated that the incorporation of adjuvants such as MDA‐7/IL‐24/IL‐7/GM‐CSF, immune checkpoint blockers, and chitosan nanoparticles enhances the functionality of DNA vaccines. 319 , 320 , 321 , 322 A noteworthy example of therapeutic DNA‐based vaccines is VGX3100, which comprises two DNA plasmids encoding HPV16/18 E6/E7 proteins. Phase III clinical trials of VGX3100 in CIN II‐III have been completed (NCT03185013 and NCT03721978), although the results have not been published yet.…”
Section: Therapeutic Interventionsmentioning
confidence: 99%
“… 15 17 Although research has shown the ability of hIL-24 to inhibit tumor cell growth and promote apoptosis, its use in treating cervical cancer is not well explored. 18 20 …”
Section: Introductionmentioning
confidence: 99%
“…[15][16][17] Although research has shown the ability of hIL-24 to inhibit tumor cell growth and promote apoptosis, its use in treating cervical cancer is not well explored. [18][19][20] To address this gap, our study investigates the specific impact of hIL-24 on SiHa and HeLa cervical cancer cells. We created a pcDNA3.1 (þ)-hIL-24 recombinant plasmid and introduced it into SiHa and HeLa cells through lipofection.…”
Section: Introductionmentioning
confidence: 99%
“…Interleukin-24 (IL-24)/Melanoma differentiation-associated gene-7(Mda-7) is a special member of the IL-10 family of cytokines that can specifically cause apoptosis in cancer cells without affecting healthy cells. The multi-functional tumor suppressing properties of Mda-7/IL-24 include: inducing apoptosis, inhibition of migration, invasion, and eventually metastasis; induction of differentiation and/or killing of cancer stem cells; sensitization of cancer cells to radiation, chemotherapy, and induction of an anti-tumor immune modulating effect [ 5 , 6 ]. Also, based on the positive results from pre-clinical and Phase I clinical trials, IL-24 has been transitioned into a phase II clinical trial, indicating that it has the potential to be safe and effective for cancer gene therapy.…”
Section: Introductionmentioning
confidence: 99%